Development of commercial web portal: Xcelearn advertisement management system (XAMS) - Muhammad Farid Zuhairi Asaraff Ali (Tanjong Malim, 2023)
Development of commercial web portal: Xcelearn advertisement management system (XAMS) by Muhammad Farid Zuhairi Asaraff Ali